Socioeconomic status and motor coordination function among children with autism - Cao, Muqing; Gu, Tingfeng; Li, Xiuhong; Jing, Jin (Frontiers in Psychiatry, 2025)
ObjectiveTo examine the association of socioeconomic status with the motor coordination impairment (probable DCD) of autism in a Chinese population.MethodsUsing cross-sectional data from the south region of China, 2020-2021, per capita family income, maternal education, and whether the only child was included as the indicators of socioeconomic status, motor coordination function was evaluated by the Developmental Coordination Disorder Questionnaire (DCDQ). We included 165 autistic children aged 2–12 years in the final analysis, among whom 88 were classified as probable DCD.ResultsAfter adjusting for covariates, the odds ratios for probable DCD among autistic children whose per capital family income was below 5000 yuan (OR: 4.77, 95% CI: 1.71-13.30) or 5000–8000 yuan (OR: 3.62, 95% CI: 1.36-9.61) per month were significantly higher than children whose per capital family income above 8000 yuan per month. Mothers without a college degree showed a decreased likelihood of probable DCD (OR: 0.33, 95%CI: 0.15-0.71).ConclusionLow income of a family is associated with a higher risk of probable DCD among autism children. The linkage between higher education of the mother and probable DCD could be attributed to more grandparenting among these families. This is the first research exploring the association between socio-demographic factors and the motor coordination function of autism. It comes from a set of low/middle-income countries with limited sources of autism in the Asian area, and comprehensive SES factors are considered. We recommend more support to autism children from low-income families, especially motor-related intervention.